Answer:
Step-by-step explanation:
Δy =-4-1 = -5
Δx =-8-(-6) = -2
distance = √((Δx)^2+(Δy)^2) = √(4+25) = √29
Answer:
304,900
Step-by-step explanation:
186,000
88,900
304,900
Answer:
<h2>10</h2>
Step-by-step explanation:
<em>The answer is 10 because 7 + 3 equals 10!</em>
<em></em>
<em>This can be proven by adding 7 + 3 or by subtracting in a certain way.</em>
<em>7 + 3 = ?</em>
<em>7 + 1 = 8</em>
<em>7 + 2 = 9</em>
<em>7 + 3 = 10</em>
<em></em>
<em>You can show more work by subtracting your answer or 10 in this case, which means that you subtract 7 by 10 or 3 by 10, either way is ok.</em>
<em></em>
<em>If you subtract 7 by 10, ( 10 - 7 ) then you get 3</em>
<em>If you subtract 3 by 10, ( 10 - 3 ) then you get 7</em>
<em>If the number you subtracted matches the number that you didn't subtract, then your answer is correct.</em>
<em></em>
<em>Hope this helps! <3</em>
<em>The result can be shown in both exact and decimal forms.
</em>
<em>Exact Form:
</em>
<em>4
e
+
21
</em>
<em>Decimal Form:
</em>
<em>31.87312731
…</em>
Thanks,
<em>Deku ❤</em>
Answer:
Step-by-step explanation:
![\tan 30 \degree = \frac{x}{ \sqrt{6} } \\ \\ \frac{1}{ \sqrt{3} } = \frac{x}{ \sqrt{6} } \\ \\ x = \frac{ \sqrt{6} }{ \sqrt{3} } \\ \\ x = \frac{ \: \sqrt{3} \times \sqrt{2} }{ \sqrt{3} } \\ \\ x = \sqrt{2}](https://tex.z-dn.net/?f=%20%5Ctan%2030%20%5Cdegree%20%3D%20%20%5Cfrac%7Bx%7D%7B%20%5Csqrt%7B6%7D%20%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B1%7D%7B%20%5Csqrt%7B3%7D%20%7D%20%3D%20%20%5Cfrac%7Bx%7D%7B%20%5Csqrt%7B6%7D%20%7D%20%20%20%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B%20%5Csqrt%7B6%7D%20%7D%7B%20%5Csqrt%7B3%7D%20%7D%20%20%5C%5C%20%20%5C%5C%20x%20%3D%20%5Cfrac%7B%20%5C%3A%20%20%5Csqrt%7B3%7D%20%20%5Ctimes%20%20%5Csqrt%7B2%7D%20%7D%7B%20%5Csqrt%7B3%7D%20%7D%20%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20%5Csqrt%7B2%7D%20)